PENGEMBANGAN MODEL SINEKTIK PADA PEMBELAJARAN MENULIS PUISI BERKONTEKS MULTIKULTURAL DALAM PEMBENTUKAN KARAKTER SISWA SMA - Sutikno Sutikno (Indonesian Language Education and Literature, 2016)
Learning to write poetry is still a monocultural means not pay attention to the diversity that exist for this. Teachers did not master the learning material to write poetry, but learning to write poetry to lift the cultural diversity in the student environment. This study focused on the model sinectic on multicultural contextual learning to write poetry. This study is specifically aimed at identifying the development needs sinectic, explained the characteristics and create a model for learning to write poetry sinectic multicultural. This research was conducted by the research design and development models sinectic multicultural learning writing poetry. Data analysis technique used is descriptive qualitative. The results of the initial test and final test, the thoroughness of the larger end of the initial tests. Initial tests were completed 57.14% and final tests are completed 100% so there is an increase of 42.86%. Based on these findings, it can be stated that the model can improve learning sinectic writing poetry have multicultural and positive impact in shaping the character of students.